Pengaruh Faktor Situasional Konsumen dalam Keputusan Pembelian pada Coffe Shop di Daerah Karawang - Syalaisha Zahra Elkautsar; Ajat Sudrajat (BADAN PENERBIT STIEPARI PRESS, 2025)
The café or coffee shop industry has experienced rapid growth in recent years in Karawang, Indonesia, in line with the changing lifestyle of modern society that increasingly values social interaction and personal well-being. Based on Susenas in 2021, the estimated population of coffee lovers in Karawang is 381,600 people. Consumer situations play an important role in shaping purchasing decisions at coffee shops. This study aims to investigate the effect of consumer situations on purchasing decisions at coffee shops in Karawang. This research is a quantitative study by collecting data through distributing questionnaires to 100 coffee shop customers in Karawang. The variables used include physical environment, social environment, time, purpose, and mood. Data analysis was carried out using multiple linear regression with the help of SmartPLS software. The results showed that the physical environment, social environment and purchase objectives had a significant effect on purchasing decisions at coffee shops. The implication of this research is that coffee shop industry players need to understand and respond better to consumer situations to improve their customer experience and business performance.